2012
DOI: 10.3171/2012.2.jns111630
|View full text |Cite
|
Sign up to set email alerts
|

Cranial nerve dysfunction following Gamma Knife surgery for pituitary adenomas: long-term incidence and risk factors

Abstract: Neurological and ophthalmological assessment in addition to routine neuroimaging and endocrinological follow-up are important to perform following GKS. Patients with a history of radiosurgery or radiation therapy are at higher risk of cranial nerve deficits. Also, a reduction in the number of isocenters delivered, along with volume treated, particularly in the patients with secretory tumors, appears to be the most reasonable strategy to minimize the risk to the visual system when treating recurrent pituitary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 26 publications
0
18
0
1
Order By: Relevance
“…Other SRS studies of perioptic tumors have reported variable results. Two large Gamma Knife (GK)-SRS studies reported a 0 and 1.9 % incidence of RION, respectively, at optic doses of 10 Gy [7, 8], but another study reported a 4 % incidence at an optic dose of 3, 1 Gy [9]. Large LINAC-SRS studies have reported a low incidence of RION of 0–2.8 % at optic doses less than 10 Gy [1012].…”
Section: Discussionmentioning
confidence: 99%
“…Other SRS studies of perioptic tumors have reported variable results. Two large Gamma Knife (GK)-SRS studies reported a 0 and 1.9 % incidence of RION, respectively, at optic doses of 10 Gy [7, 8], but another study reported a 4 % incidence at an optic dose of 3, 1 Gy [9]. Large LINAC-SRS studies have reported a low incidence of RION of 0–2.8 % at optic doses less than 10 Gy [1012].…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant improvements in neuroimaging modalities, radiosurgical equipment, and treatment planning software, even recent series from widely experienced clinical centers have reported complication rates of 4-10% after radiosurgery for pituitary adenomas and parasellar meningiomas. 5,56) Similarly, treatmentrelated morbidity related to cranial neuropathy was marked in 7% of our patients. Oculomotor and abducens nerves were affected most frequently, but only transiently in 7 of 8 cases.…”
Section: Radiosurgery For Cavernous Sinus Tumorsmentioning
confidence: 99%
“…In a recent publication from the respected radiosurgical group at Yale University, the authors detailed their experience using a margin dose of 35 Gy for patients with functioning pituitary adenomas. 4 In a cohort of 31 patients with a mean follow-up of 40.2 months and relatively small adenoma sizes (mean 739 mm 3 , range 483-996 mm 3 ), initial endocrine remission was achieved in 70% of patients; however, at the last follow-up, 48% of patients remained in endocrine remission off medications. 4 This endocrine remission rate is not markedly different from those in published studies using moderate doses.…”
Section: Disclosurementioning
confidence: 99%
“…6,10,14 For pituitary adenomas, particularly functioning ones, the relationship between dose and endocrine remission warrants additional investigation-the higher the delivered dose, the more likely that hypopituitarism and cranial nerve deficits will occur following radiosurgery. 3,13 While hypopituitarism is a manageable complication following radiosurgery, radiation-induced cranial neuropathies can be much more challenging and less satisfactorily addressed. There may, in fact, be diminishing returns for doses greater than 25 Gy in patients with functioning adenoma.…”
Section: Disclosurementioning
confidence: 99%